Offshore financial centres in decisions of private EU investors. Perspectives of further development - Brodzka, Alicja (Centra finansowe offshore w decyzjach finansowych Europejczyków. Perspektywy rozwoju, 2011)
The article presents the subject of offshore financial centres from the perspective of an individual European investor. It analyzes the effects of European regulations, introduced as an answer to the increasing competitive role of third-party territories employing elaborate systems of tax incentives. The research also presents perspectives for offshore financial centres, forced to adapt to the changed legal environment
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 101-114
Keywords: offshore financial centres; European Savings Directive; tax information exchange